2022
DOI: 10.1016/j.tust.2021.104300
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and field validation on soil clogging of EPB shields in completely decomposed granite

Abstract: Clogging may occur inside the shield machine during earth pressure balance (EPB) tunnelling in cohesive soils. Soil conditioning can be used to reduce clogging potential and ensure the efficiency of the shield tunnelling. The current methods used to assess the clogging potential mainly focus on pure clayey soils or artificial mixed soils, the clogging in natural weathered soils is less studied. This paper studied the clogging when tunnelling in completely decomposed granite by laboratory tests, followed by fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Hassanpour et al (2010) analyzed the performance of a double shield TBM in pyroclastic rocks, noting that water indirectly affects machine performance due to its effect on the strength and alteration of the rock mass. Increasing water content causes problems, especially in excavating clay-rich and fine-grained soil and rock formations, and many researchers investigated these problems, especially clogging, for TBM excavations (Thewes and Burger 2005;Hollmann and Thewes 2013;Chen et al 2022). Chen et al (2022) emphasized that clogging will reduce the penetration rate of cutters, resulting in excessive wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassanpour et al (2010) analyzed the performance of a double shield TBM in pyroclastic rocks, noting that water indirectly affects machine performance due to its effect on the strength and alteration of the rock mass. Increasing water content causes problems, especially in excavating clay-rich and fine-grained soil and rock formations, and many researchers investigated these problems, especially clogging, for TBM excavations (Thewes and Burger 2005;Hollmann and Thewes 2013;Chen et al 2022). Chen et al (2022) emphasized that clogging will reduce the penetration rate of cutters, resulting in excessive wear.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing water content causes problems, especially in excavating clay-rich and fine-grained soil and rock formations, and many researchers investigated these problems, especially clogging, for TBM excavations (Thewes and Burger 2005;Hollmann and Thewes 2013;Chen et al 2022). Chen et al (2022) emphasized that clogging will reduce the penetration rate of cutters, resulting in excessive wear. In addition, many studies showed similar results for TBMs' disc cutters (Peila et al 2019;Avunduk and Copur 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on current engineering experience, both slurry pressure balance (SPB) and Earth pressure balance (EPB) shields can face clogging issues in clayey strata (Chen et al, 2022;. To mitigate shield clogging during EPB tunneling, soil conditioning chemicals are frequently injected ahead of the cutter head (Martinelli et al, 2015;Zumsteg and Langmaack, 2017;Liu et al, 2018;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of urban rail transit construction, subway shield construction has been widely used with its unique advantages [1]. The EPB shield tunneling in Beijing is often carried out in sandy gravel soil [2][3][4], and the excavated soil mass in the natural state cannot meet the requirements of plastic fluidization of soil mass [5][6][7]. Therefore, this can easily lead to the instability of the excavation surface [8][9][10][11][12], and cause the closure of the pressure chamber [13][14][15], the caking of the pressure chamber [16], gushing [17,18], and other technical problems often encountered in the construction of soil layers.…”
Section: Introductionmentioning
confidence: 99%